EKSEKUSI HAK PATEN YANG DIBEBANKAN DENGAN JAMINAN FIDUSIA - Ginting Suka, Pio Salvator; Sri Indrawati, Anak Agung (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 06, Oktober 2014, 2014)
In the progression economic development, should also be accompanied by thedevelopment of the maximum law. But in reality, the law is always behind theconstruction of the development that need by society. Currently, fiduciary, evolvetoward more advanced as well as many objects fiduciary evolve toward newer. Forexample, patents are charged with a fiduciary, but the execution of the patent has notbeen clearly set out in Fiduciary Act Number. 42 of 1999. Therefore, this paper madetitled "Execution Patents Charged With Fiduciary”. By using the normative method ofwriting, this article will provide knowledge about the execution process patent if thedebtor defaults. In UUJF, no mention of how the execution process patent if the debtordefaults, but in the Patents Act Number. 14 of 2001 is set way transfer of patents thatcan be used as an execution in a fiduciary patents is through the transfer of patentrights in writing made in the form of certificate notary and registered / recorded in theDirectorate General of Intellectual Property Rights (IPR DG) and the administrativecost. The transfer of patent rights writing is intended to capitalize on the inherenteconomic rights in patents by patent licensees. Furthermore, from the results obtainedthrough the implementation of the economic rights of repayment of debt taken bycreditors.
Keywords: Fiduciary, Patents, Process Execution